2013
DOI: 10.15376/biores.8.1.1361-1373
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl Acetate Modified Scots Pine Reinforced HDPE Composites: Influence of Various Levels of Modification on Mechanical and Thermal Properties

Abstract: In order to compare the effect of vinyl acetate modification (VA) at different levels of weight percentage gain, Scots pine wood flour was modified with VA to three different wt% gains (10%, 16%, and 21% WPGs). Acetic anhydride (AA) modification at 24% WPG was also studied. Modified Scots pine wood flour reinforced HDPE composites (WPCs) were produced at 30 wt% wood flour loading by using extrusioninjection molding process and the mechanical properties of WPCs were determined. The thermal and morphological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that chemically modified natural reinforcing materials (wood/plant fiber and microcrystal cellulose) contribute to the improvement of the interfacial adhesion ability with thermoplastic polymers (HDPE and PP). Such results were obtained in studies on widely used thermoplastic composite production methods (press moulding and injection moulding) (Özmen et al 2013;Çetin et al 2015;Narlıoğlu 2018). For this reason, it is thought that chemically modified (with butyric anhydride) wood flour will contribute to the properties of wood-PLA composite filaments.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…It has been reported that chemically modified natural reinforcing materials (wood/plant fiber and microcrystal cellulose) contribute to the improvement of the interfacial adhesion ability with thermoplastic polymers (HDPE and PP). Such results were obtained in studies on widely used thermoplastic composite production methods (press moulding and injection moulding) (Özmen et al 2013;Çetin et al 2015;Narlıoğlu 2018). For this reason, it is thought that chemically modified (with butyric anhydride) wood flour will contribute to the properties of wood-PLA composite filaments.…”
Section: Introductionmentioning
confidence: 70%
“…It has been reported that the thermal degradation temperatures of hemp fibers after chemical modification increased by about 15 °C compared to unmodified ones (Özmen 2012). In other studies, it has been reported that the thermal decomposition temperatures of composites increased as a result of the addition of modified wood/plant fibers into the thermoplastic polymer compared to the neat polymer and unmodified wood/fiber added composites (Özmen et al 2013;Çetin et al 2015;Narlıoğlu 2018). In this study, it is speculated that the degradation of MWF-added composites at higher temperatures compared to UMWF-added composites can be attributed to the reduced free hydroxyl groups after chemical modification.…”
Section: Fig 5 Tga Analysis Values and Thermograms Of 3d Printed Samplesmentioning
confidence: 94%
“…Samples of about 3 g were then extracted in a Soxhlet apparatus (Gerhardt EV6 All/16 No. 10-0012) for 5 h using a 300 mL solution of toluene-ethanol-acetone (4:1:1 by volume) (Sluiter et al, 2008;Özmen et al, 2013). For each sample, the final residue was dried at 50 • C for 12 h. and the resulting residue was designated as cell wall residue (CWR).…”
Section: Cell Wall Isolationmentioning
confidence: 99%
“…Small ground samples of about 3 g were extracted in a Soxhlet apparatus (Gerhardt EV6 ALL/16 No. 10-0012) for 5 h using a 300 mL solution of toluene-ethanol-acetone (4:1:1 by volume) (Sluiter et al, 2008;Özmen et al, 2013). For each sample, the final residue was dried again at 50 • C for 12 h prior to further analysis.…”
Section: Chemical Analysis Of Bast Fibersmentioning
confidence: 99%